2013
DOI: 10.2807/ese.18.22.20489-en
|View full text |Cite
|
Sign up to set email alerts
|

Epidemic diffusion of KPC carbapenemase-producing Klebsiella pneumoniae in Italy: results of the first countrywide survey, 15 May to 30 June 2011

Abstract: Carbapenem-resistant Enterobacteriaceae (CRE) are emerging as a public health problem in various settings. In Italy, a rapid and remarkable increase of carbapenem-non-susceptible Klebsiella pneumoniae has been reported since 2010. Here we report on the results of a countrywide cross-sectional survey, carried out from 15 May to 30June 2011 to investigate the diffusion of CRE in Italy and to characterise the most prevalent resistance mechanisms and their dissemination patterns. CRE were reported from most (23 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(55 citation statements)
references
References 52 publications
4
48
2
1
Order By: Relevance
“…We observed that patients with BSI due to KPC-Kp resistant to both meropenem/vaborbactam and ceftazidime/avibactam had a short colonization time, thus suggesting that cross-resistance did not result from selection pressure due to recently antimicrobial therapy. Therefore, considering the high incidence of KPC-Kp strains in our country, it is plausible that patients acquired cross-resistant strains during hospitalization or that meropenem/vaborbactam and ceftazidime/avibactam resistance emerged after prolonged antimicrobial treatments in colonized patients [20]. Overall, clinical and microbiological failure was observed in two out of three patients with pneumonia, while no specific treatment was associated to clinical success.…”
Section: Discussionmentioning
confidence: 94%
“…We observed that patients with BSI due to KPC-Kp resistant to both meropenem/vaborbactam and ceftazidime/avibactam had a short colonization time, thus suggesting that cross-resistance did not result from selection pressure due to recently antimicrobial therapy. Therefore, considering the high incidence of KPC-Kp strains in our country, it is plausible that patients acquired cross-resistant strains during hospitalization or that meropenem/vaborbactam and ceftazidime/avibactam resistance emerged after prolonged antimicrobial treatments in colonized patients [20]. Overall, clinical and microbiological failure was observed in two out of three patients with pneumonia, while no specific treatment was associated to clinical success.…”
Section: Discussionmentioning
confidence: 94%
“…Carbapenem resistance was initially slow to emerge in Enterobacteriaceae but is now steadily increasing, and mediated more and more by acquired carbapenemases (predominantly by KPC, VIM, IMP, NDM and OXA-48-like types) [33][34][35][36] 41 . This clone also spread widely earlier in the USA 42 and then in Israel 43 , where an aggressive, nationwide infection control intervention was successful in bringing it under control 44,45 .…”
Section: Carbapenem Resistancementioning
confidence: 99%
“…(9184) 34 ((brl adj '17421') or brl17421 or (thiophenemalonamic adj acid) or negaban or temocillin or temopen).ti,ab. ( 179 41 (adelanin or alcomicin or apigent or apogen or apoten or azupel or bactiderm or biogaracin or bristagen or cidomycin or danigen or dermogen or dianfarma or dispagent or duragentam$ or epigent or (frieso adj gent) or garabiotic or garalone or garamicin$ or garamycin or garbilocin or gencin or gendril or genoptic or genrex or gensumycin or gentabiotic or gentabiox or gentac or gentacidin or gentacin or gentacor or gentacycol or gentacyl or gentafair or gentagram or gentak or gental or gentaline or gentalline or gentalol or gentalyn or gentamax or gentame$ or gentamicin$ or gentamina or gentamycin$ or gentamyl or gentamytrex or gentaplus or gentarad or gentasil or gentasol or gentasone or gentasporin or gentatrim or gentavet or genticin$ or genticyn or gentiderm or gentimycin or gentocin or gentogram or gentomycin or genum or geomycine or gevramycin or g-mycin or gmyticin or g-myticin or grammicin or hexamycin or jenamicin or konigen or lacromycin or lisagent or martigenta or migenta or miragenta or miramycin or nichogencin or nsc 82261 or nsc82261 or obogen or ocugenta or ocu-mycin or oftagen or ophtagram or opthagen or optigen or opti-genta or ottogenta or pyogenta or refobacin or ribomicin or rigaminol or rocy gen or rovixida or rupegen or sagestam or sch 9724 or sch9724 or sedanazin or servigenta or skinfect or sulmycin or tangyn or u-gencin or versigen or yectamicina).ti,ab. (19829) 43 (akacin or akicin or amicacina or amicasil or amicin or amiglymide v or amikacin$ or amikafur or amikalem or amikan or amikayect or amikin or amiklin or amikozit or amiktam or amitracin or amixin or amukin or apalin or bb k 8 or bb k8 or bbk 8 or bb-k 8 or bbk8 or bbk-8 or bb-k8 or biclin or biklin or biokacin or briclin or briklin or chemacin or cinmik or fabianol or gamikal or glukamin or kacinth-a or kanbine or kormakin or likacin or lukadin or miacin or mikasome or onikin or oprad or orlobin or pediakin or pierami or riklinak or savox or selaxa or selemycin or sulfate amikacin or tybikin or vs 107 or vs107 or yectamid).ti,ab.…”
Section: Critical Appraisalmentioning
confidence: 99%
“…The genetic analysis of 178 IRCCS-ISMETT K. pneumoniae clinical isolates showed that they belong to several STs, including 37 ST258, 28 ST307 and 51 ST512. In Italy, CRE K. pneumoniae strains are predominantly one of these three STs [ 35 , 36 ]. Out of 178 K. pneumoniae isolates, 163 belonged to the O2afg serotype, i.e., 91.6%.…”
Section: Resultsmentioning
confidence: 99%